Serious game prototype for nurses on nipple-areolar lesions resulting from fungal infections in breastfeeding - Lays Pinheiro de Medeiros; Luana Souza Freitas; Anna Alice Carmo Gonçalves; Iasmin Freitas Bessa; Rhayssa de Oliveira e Araújo; Isabelle Katherinne Fernandes Costa (PLoS ONE, 2026)
Background Despite the advantages, breastfeeding can be a difficult and painful process, especially due to the occurrence of nipple-areolar lesions due to fungal infection. Objective: Develop and validate a breastfeeding software program using a game to be used as an educational tool. Methodology An educational software program, the serious game “AleitaGame”, was developed through applied, methodological, quantitative and cross-sectional research. Clinical cases were constructed through a Scoping Review and the media resources and content were chosen. The software, the narrative, the clinical aspects and the context were then validated by experts. Results The construction of the clinical case presented and the scenario of a nipple-areolar lesion resulting from a fungal infection was based on 40 scientific documents. The product was then evaluated by two groups of judges. Conclusion The study allowed the development and validation of the prototype of serious game on nipple-areolar lesions resulting from fungal infections. The game covers historical content, anamnesis and relevant clinical parameters, the game received good evaluation scores from the judges and it is expected that at the end the player will recognize a nipple-areolar injury, identify signs and symptoms and carry out treatment, monitoring and prevention.